(untitled) (Publicaciones en Ciencias y Tecnología, 2022)
Wastewater from the fishmeal production industry has a high content of organic matter, turbidity and fats, which makes its treatment and final disposal difficult. Therefore, this study focuses on evaluating the efficacy of coagulants of natural origin versus synthetic coagulants, as a function of turbidity and the factors that influence it by applying an experimental quantitative study. The natural coagulants used were Aloe vera gel and Selenicereus Undatus pitahaya mucilage, while the coagulants of chemical origin were aluminum polychloride (PAC) and aluminum sulfate. So that to the high concentration of fat present in the discharge water with respect to the reference value, a pre-sedimentation of the water was carried out without any type of mechanical or coagulating action, resulting in the elimination of fats of 92%.The initial turbidity of the wastewater was 1230.33 NTU, obtaining turbidity removal percentages for PAC, aluminum sulfate, pitahaya and Aloe vera in the order of 99.58%, 99.87%, 62.26%, 75.15%, respectively. On the other hand, the COD for the most efficient synthetic coagulant and natural coagulant, was 18 mgO2/L and 839.35 mgO2/ correspondingly. This study aims to promote the use of friendly resources for the environment, guaranteeing an efficient removal of contamination from the aqueous environment.